Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/0883073813512899
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Perinatal Risk Factors for Autism Spectrum Disorder in a New Jersey Cohort

Abstract: This study evaluated the prevalence of pre- and perinatal risk factors in a cohort of children with autism spectrum disorders compared with the New Jersey population. Our cohort included 268 individuals with an autism spectrum disorder. Birth histories were obtained by a self-administered questionnaire. The autism spectrum disorders cohort rates of 7 perinatal risk factors were significantly higher than New Jersey state rates: mother's age 35 years or older, low birth weight, multiple gestation, prematurity, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 32 publications
2
37
0
1
Order By: Relevance
“…Ornoy et al (2015) reviewed ASD environmental risk factors and reported 17 significant prenatal, perinatal, and postnatal risk factors: maternal inflammation and immune activation, rubella, cytomegalovirus (CMV), influenza, fever, diabetes, folic acid deficiency, toxoplasmosis; exposure to ethanol, cocaine, valproic acid, misoprostol, thalidomide, antidepressant serotonin reuptake inhibitors (SSRIs); and exposure to pesticides, insecticides, and air pollution. Also, Maramara et al (2014) found 15 significant ASD prenatal, perinatal, and postnatal risk factors in a single study sample: father's age, mother's age, maternal drug and alcohol use, maternal hypertension during pregnancy, gestational diabetes, vaginal bleeding, cesarean section, prematurity, induced labor, prolonged labor, lack of infant oxygen during delivery, low birth weight, newborn jaundice, and newborn infection.…”
Section: Environmental Syndromic Asd Has Been Found With Varied Brainmentioning
confidence: 94%
See 2 more Smart Citations
“…Ornoy et al (2015) reviewed ASD environmental risk factors and reported 17 significant prenatal, perinatal, and postnatal risk factors: maternal inflammation and immune activation, rubella, cytomegalovirus (CMV), influenza, fever, diabetes, folic acid deficiency, toxoplasmosis; exposure to ethanol, cocaine, valproic acid, misoprostol, thalidomide, antidepressant serotonin reuptake inhibitors (SSRIs); and exposure to pesticides, insecticides, and air pollution. Also, Maramara et al (2014) found 15 significant ASD prenatal, perinatal, and postnatal risk factors in a single study sample: father's age, mother's age, maternal drug and alcohol use, maternal hypertension during pregnancy, gestational diabetes, vaginal bleeding, cesarean section, prematurity, induced labor, prolonged labor, lack of infant oxygen during delivery, low birth weight, newborn jaundice, and newborn infection.…”
Section: Environmental Syndromic Asd Has Been Found With Varied Brainmentioning
confidence: 94%
“…There are fewer defined environmental ASD syndromes than genetic ASD syndromes, but there are numerous ASD environmental risk factors (Boukhris et al 2015;Croen et al 2011;Grabrucker 2013;Hviid et al 2013;Lyall et al 2014;Maramara et al 2014;Ornoy et al 2015;Rossignol et al 2014;Schieve et al 2014). Ornoy et al (2015) reviewed ASD environmental risk factors and reported 17 significant prenatal, perinatal, and postnatal risk factors: maternal inflammation and immune activation, rubella, cytomegalovirus (CMV), influenza, fever, diabetes, folic acid deficiency, toxoplasmosis; exposure to ethanol, cocaine, valproic acid, misoprostol, thalidomide, antidepressant serotonin reuptake inhibitors (SSRIs); and exposure to pesticides, insecticides, and air pollution.…”
Section: Environmental Syndromic Asd Has Been Found With Varied Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, premature birth further increases the risk of autism spectrum disorders in patients without known autism-related genetic mutations [3]. A recent epidemiological report singles out hypoxia at birth as the only risk factor significantly more prevalent in older mothers of the children with autism spectrum disorders compared to younger mothers [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Cytokines also influence neuronal proliferation and differentiation, which is also related to ASD (40). The increased risk has also been confirmed for preeclampsia and pregnancy bleeding, before the 20 th gestational week (38,41). In a systematic review done in 2012, the factors identified as main pregnancy-related ASD risk factors were pregnancy bleeding and preeclampsia (28).…”
Section: Maternal State/pregnancy Complicationsmentioning
confidence: 97%